Optimalisasi Zakat Profesi Guru ASN: Peran UPZ, Pemotongan Langsung, dan Sosialisasi BAZNAS Parepare - nurlia nurlia; Hannani; Firman; St. Nurhayati Ali; Rukiah; Saldi (Indonesia Journal of Zakat and Waqf, 2024)
This study explores the optimization of professional zakat collection among civil servant teachers (ASN) in Parepare City, focusing on the roles of Zakat Collecting Units (UPZ), direct salary deductions, and BAZNAS socialization programs. Using a qualitative field study approach, data were gathered through observation, interviews, and documentation at BAZNAS Parepare. The findings reveal a substantial zakat potential from ASN teachers, estimated at IDR 2,706,480,000 annually, yet the actual collection in 2022 only reached about IDR 600,000,000. The gap is attributed to limited knowledge regarding zakat obligations, economic constraints, and the distribution of zakat funds to various amil zakat institutions. BAZNAS Parepare has implemented strategic measures, including establishing UPZ in government agencies, direct zakat deductions from salaries, and intensive socialization to increase awareness and compliance. The collected zakat is allocated to eight eligible groups (asnaf), with a focus on economic empowerment programs such as business capital assistance and productive facilities for mustahik. These initiatives have shown positive impacts, enabling some mustahik to become muzakki. The study concludes that optimizing professional zakat, especially from ASN teachers, can significantly contribute to poverty alleviation and economic empowerment in Parepare. Further efforts are needed to enhance zakat literacy, strengthen regulations, and innovate collection methods for maximum impact.